When Inflation Again Matters: Do Domestic and Global Output Gaps Determine Inflation in the EU? - Jana Budova; Veronika Sulikova; Marianna Sinicakova (Amfiteatru Economic, 2023)
In this paper, we examine whether domestic or global output gap affects inflation in three panels: the European Union, the peripheral countries of the European Union, and the Eurozone. We have also analysed the impact of these variables on inflation in individual countries of the European Union. To find the determinants of inflation, we employ the Granger causality test and panel regression. The first examined period is from 1Q 1997 to 3Q 2020. The period between 1999 and 2020 is divided into two shorter periods – the precrisis (1999 – 2008) and postcrisis (2009-2020) period. The results of the study show that after the crisis the global output gap predicts the evolution of inflation in the Eurozone panel. On the other hand, the domestic output gap predicts inflation in the European Union. In the precrisis period, the determinant of inflation is the domestic output gap, specifically in the Eurozone panel. In the European Union panel and its peripheral economies, the global output gap determines inflation. In Italy, Lithuania, Estonia, Finland, Latvia, and the Netherlands, the domestic output gap determines inflation. The global output gap determines inflation in the Netherlands, Slovenia, Estonia, and Latvia. We demonstrated that there are two ways dependency among the variables.
Keywords: E31; E32; E58; 330; domestic output gap; global output gap; inflation; the Granger causality test; panel data model.